EXAMINING CORPORATE TAXPAYERS' INTENTION TO USE CORETAX THROUGH THE THEORY OF PLANNED BEHAVIOR PERSPECTIVE - Izyana Afiqah Agustrianti; Yusnaini Yusnaini (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2026)
Digital transformation in the field of taxation has prompted the Directorate General of Taxes to implement the Coretax system as an effort to modernize tax administration. However, the adoption rate of this system by taxpayers still faces various obstacles. The main problem lies in the behavior and readiness of taxpayers to accept and use the Coretax system optimally. The low utilization of Coretax has the potential to hamper the effectiveness of tax reform and the achievement of tax compliance. Therefore, it is important to examine the behavioral factors that influence taxpayers' intentions to adopt Coretax in order to support the successful implementation of the system. This study uses a quantitative approach with a population of all taxpayers in Palembang City. A sample of 150 respondents was obtained through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression based on the Theory of Planned Behavior to test the influence of attitudes, subjective norms, and perceived behavioral control. The results show that attitude, subjective norms, and perceived behavioral control have a positive and significant effect on the intention to use Coretax. These findings conclude that psychological and social factors play an important role in the adoption of the system. Implicitly, the tax authorities need to strengthen education, socialization, and technical support for taxpayers. Keywords: Coretax, Theory of Planned Behavior, Intention to Use, Taxpayers, Digital Taxation Transformation.